Mathematics and Combinatorial Thinking: How Computational Ability Influences Problem-Solving in Number Patterns? - Tiffani, Khatriya; Manaf, Mohammed Rizzman; Efendi, Riswan (Interval: Indonesian Journal of Mathematical Education, 2025)
Purpose of the study: This study aims to analyze students' computational thinking abilities in solving combinatorial problems based on high, medium, and low ability categories. Methodology: This study uses a descriptive qualitative approach with subjects of 33 students of class VIII I State Islamic Junior High School 2 Bondowoso. Data were collected through written tests, semi-structured interviews, and documentation. Data analysis used the Miles and Huberman model (reduction, presentation, conclusion) with triangulation techniques for validation, comparing test results, interviews, and documentation. Main Findings: Students with high and medium computational abilities are able to meet all indicators of computational thinking, including identifying and understanding problems, and converting them into combinatorics. Meanwhile, students with low abilities have difficulty in re-understanding the problems found. Novelty/Originality of this study: This study provides new insights into how students' level of computational thinking ability influences their success in solving combinatorial problems, as well as offers perspectives in developing more effective learning strategies to enhance students' computational thinking ability.